Prolongation of absence seizures and changes in serotonergic and dopaminergic neurotransmission by nigrostriatal pathway degeneration in genetic absence epilepsy rats - KARAMAHMUTOĞLU, TUĞBA (Elsevier Inc., 2022)
Objective: Basal ganglia structures play an important role in the pathophysiology of absence epilepsy, known as remote control of absence seizures. We examined the role of the nigrostriatal dopaminergic pathway in absence epilepsy through behavioral and electroencephalography (EEG) parameters, immunohistochemical, and biochemical characteristics of dopamine and serotonin in the genetic absence epilepsy rat model. Methods: The nigrostriatal pathway was degenerated by the injection of chemical 6-hydroxydopamine hydrobromide (6-OHDA) into the medial forebrain bundle (MFB) in Wistar and genetic absence epilepsy rats from Strasbourg (GAERS). On the 21st day after stereotaxic surgery, spike-and-wave discharges (SWDs) on EEG were recorded in GAERS groups. Thereafter, Wistar-Control, GAERS-Control, Wistar-6OHDA, GAERS-6OHDA rats were subjected to the cylinder and apomorphine-induced rotation tests. Dopaminergic or serotonergic immunoreactivity was examined in the cortex, striatum, and substantia nigra pars compacta. High-performance liquid chromatography method was used for biochemical analysis of dopamine and serotonin in the cortex and thalamus. Results: In behavioral analysis, the number of rotations in the GAERS-6OHDA group was significantly higher than in Wistar-6OHDA rats. The degeneration of the nigrostriatal dopaminergic pathway produced a significant increase in the cumulative duration of SWDs and the duration of each SWD in GAERS-6OHDA rats. GAERS-Control rats displayed significantly higher cortical and striatal serotonin immunoreactivity and cortical serotonin level compared to Wistar-Control animals. Moreover, cortical and striatal serotonin immunoreactivity and cortical serotonin levels increased in Wistar-6OHDA and GAERS-6OHDA groups compared to their control groups. Significance: The effect of 6-OHDA-induced MFB lesion on absence epilepsy was examined for the first time by comparing Wistar and GAERS rats. The nigrostriatal dopaminergic pathway as a part of the remote-control system is likely to participate in the seizure network. © 2022 Elsevier Inc.
Keywords: 6-OHDA; Basal ganglia; Epilepsy; GAERS; Medial forebrain bundle; Wistar